2006
DOI: 10.1080/02699050601049874
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of components of memory in post-traumatic amnesia

Abstract: The pattern of recovery of memory and new learning during PTA reflects a number of complex, inter-related variables including; the familiarity with the information, amount of rehearsal both before and since the accident and the number of cues available in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…In contrast, in a study using a composite PTA scale that included items from the OPTAS, the GOAT and the WPTAS, recognition memory (but not memory recall) recovered significantly before orientation (Tate et al, 2000). When sequence of recovery was examined in more detail across the studies, orientation to person was always found to recover first (Geffen et al, 1991;Gronwall & Wrightson, 1980;High et al, 1990;Leach et al, 2006;McFarland et al, 2001;Tate et al, 2000). The order in which orientation to place and time and memory were recovered has remained unclear.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…In contrast, in a study using a composite PTA scale that included items from the OPTAS, the GOAT and the WPTAS, recognition memory (but not memory recall) recovered significantly before orientation (Tate et al, 2000). When sequence of recovery was examined in more detail across the studies, orientation to person was always found to recover first (Geffen et al, 1991;Gronwall & Wrightson, 1980;High et al, 1990;Leach et al, 2006;McFarland et al, 2001;Tate et al, 2000). The order in which orientation to place and time and memory were recovered has remained unclear.…”
mentioning
confidence: 71%
“…It has been suggested that differences in the items included to measure the same constructs on different PTA scales may account for the variations in sequences of recovery described above (Leach et al, 2006;McFarland et al, 2001). Essentially, Leach et al (2006) pointed out that the inconsistencies may be partially due to orientation and memory being "ill-defined constructs which are indexed by summing up variable groups of items" (p. 1242).…”
mentioning
confidence: 94%
See 3 more Smart Citations